Transcatheter Closure of Atrial Septal Defect: One Center Experience and Mid-Term Follow-Up - Fellat, Pr. Nadia; Ibenchekroun, Dr. Meryem; Fellat, Pr. Rokaya (RA Journal Of Applied Research, 2023)
Objectives: The aim of this study is to present our center’s experience with device closure of atrial septal defects. Introduction: Atrial septal defects (ASD) constitute the most frequent congenital heart disease in adults and ostium secundum (OS) is the most common type. Device closure of ASD is currently accepted as the treatment of choice. Methods: Retrospective study, over a five-year period from 2016 to 2021. All patients who benefited from OS-ASD closure were included. Results: Twenty-three patients were recruited. All patients had a significant shunt. The majority were female (69,9%) and the average age was 30,39 years; age range 6 – 70. The average hospital admission time was 3 ± 1 days. Dyspnea (≥ NYHA II) was noted in 62%. Closure success rate was 95,7%. During Follow up, an improvement in functional status was observed in all cases. A significant decrease in right cavities dilatation as well as pulmonary arterial pressure has been reported. Conclusion: Device closure of secundum atrial septal defects demonstrates a high procedural success rate with a low incidence of complications in the follow up period.